HUBUNGAN PENGETAHUAN DENGAN KEJADIAN ULKUS DIABETIK PASIEN DIABETES MELLITUS DI RUANG PERAWATAN BEDAH RSUD DR. MM. DUNDA LIMBOTO KABUPATEN GORONTALO TAHUN 2013 - Muh. Isman Jusuf; Fadli Syamsuddin (-, 2021)
Diabetic ulcers is one of the common complications that commonly occur in patients with diabetes mellitus. In order to prevent the disease, it requires the effective and efficient treatment of both pharmacological and non-pharmacological treatment. The purpose of this study is to determine the relationship between the knowledge and the cases of diabetic ulcers of patients with diabetes mellitus. The type of this study is analytic survey with a cross-sectional study, with a sample of 64 people. The result was processed in univariate and bivariate between knowledge and the cases of diabetic ulcers among patients with diabetes mellitus. The suggestions of this study are addressed to the management of Dr. MM Dunda Hospital, Limboto, in order to further improve the knowledge about diabetes through the dissemination of pamphlets, leaflets and posters to patients in hospital. So, the patients canan read more information about the diabetes mellitus and the prevention of diabetic ulcer cases.